Lifestyle, homocysteine levels and the risk of cardiovascular disease among Catholics living in the South of Poland - Majda, Anna; Zalewska-Puchała, Joanna; Kamińska, Alicja; Bodys-Cupak, Iwona; Suder, Marcin (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction: Public health specialists and nurses are interested in identifying the elements of lifestyle that prevent disease in specific human populations, including religious groups. Aim: The term lifestyle Catholic compound with the level of homocysteine in blood serum, as a risk factor for cardiovascular disease (CVD). Material and Methods: The cross-sectional study was conducted among 134 Catholics. Use of a questionnaire of own authorship, the International Physical Activity Questionnaire, Inventory Behavioral Health (HBI), Scale Experienced Stress PSS-10, laboratory tests (homocysteine), Test Fagerström Nicotine Dependence. Results: In more than half of Catholics diagnosed increased homocysteine levels. Knowledge of about halves of the respondents on CVD was fully satisfactory. Selected elements of life style Catholics, like physical activity, addictions, perceived stress, health behaviors in the HBI, psychosocial factors and diet deviate from the recommendations relevant to the prevention of CVD and were not significantly linked to the performance level of homocysteine in the blood serum, with the exception of a significant relationship between its proper level and the consumption of milk, whole wheat flakes, pasta and wheat groats and also not smoking cigarettes. Conclusions: Public health professionals and nurses should develop culturally specific educational interventions, taking into the life style and homocysteine levelaccount cardiovascular risk factors among followers of different religions.